2018
DOI: 10.1038/s41391-018-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lower urinary tract symptoms on mortality: a 21-year follow-up among middle-aged and elderly Finnish men

Abstract: Background: The usefulness of lower urinary tract symptoms (LUTS) as mortality risk factors remains unclear. Repeated assessments are required to take into account symptom fluctuation and de novo symptom appearance. The study objective was to evaluate mortality in relation to three urinary storage symptoms-urgency, daytime frequency and nocturia-in middle-aged and elderly men, considering also other time-varying factors during follow-up. Methods: A mail survey of a population-based cohort of men initially aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Ten original full text articles and 1 conference abstract provided data on nocturia associated death, including 19,590 men and 14,241 women with a total followup of 297,379 person-years (table 1). 21e32 Five of the 11 authors (45%) confirmed the accuracy of our data extraction, 22,25,27,29,31 2 (18%) corrected some errors or provided additional information 26,32 and 4 (36%) were unable respond to our requests for data checks and clarifications. 21,23,28,30 Studies were done on 3 continents in male and mixed gender populations varying widely in age distribution and followup (table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 93%
“…Ten original full text articles and 1 conference abstract provided data on nocturia associated death, including 19,590 men and 14,241 women with a total followup of 297,379 person-years (table 1). 21e32 Five of the 11 authors (45%) confirmed the accuracy of our data extraction, 22,25,27,29,31 2 (18%) corrected some errors or provided additional information 26,32 and 4 (36%) were unable respond to our requests for data checks and clarifications. 21,23,28,30 Studies were done on 3 continents in male and mixed gender populations varying widely in age distribution and followup (table 1).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 93%
“…BPE, one of the most common diseases in middle-aged men, is a representative disease that causes lower urinary tract symptoms and the enlargement of the prostate gland, which blocks the urethra and induces urinary disorders. BPE, which occurs due to aging and an imbalance of male hormones, may lead to serious complications, such as urethrostenosis, bladder stones, hematuria, acute urinary retention, renal failure, etc., which lowers patients' quality of life [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In another US study of older men (mean age 74), those who voided three or more times per night had a 21 per cent greater risk of mortality than those with zero to one voids, also after controlling for important covariates (Endeshaw et al, 2016). In Finland, Akerla et al (2018) analysed longitudinal survey data of middle-aged and elderly men and, controlling for important covariates, found that those with nocturia had a 38 per cent greater risk of mortality than those without, where nocturia was defined as two or more voids per night. Nakagawa et al, (2010) analysed the association between nocturia and mortality in a community-based sample of older Japanese individuals (aged 70 years or above), also using longitudinal survey data.…”
Section: Nocturia and Health Social And Work Outcomesmentioning
confidence: 98%